Management of Oral Sub-Mucous Fibrosis: An update - Sadat, SM Anwar; Benzadid, Md Shadly; Nusrath, Muzzammil; Rita, Sufia Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Oral submucous fibrosis (OSMF) is a complex, debilitating, and precancerous condition. Formerly restricted to the Indian subcontinent, it is now frequently seen in the Asian communities of the United Kingdom, the United States, and other developed countries, and thus constitutes a severe global health problem. Areca-nut, the well-known causative agent of the disease, is now recognized as a group one carcinogen. Several grading systems and management protocols have been published in the literature to deal with this progressive disease.Despite the numerous medical methods used in oral sub mucous fibrosis management, sometimes surgical intervention becomes inevitable. Here, we extensively reviewed existing literature to discuss about incidence, presentation, aetio-pathogenesis, medical and surgical management with outcome of OSMF J Bangladesh Coll Phys Surg 2020; 38(3): 135-144